Gravimetric Monitoring of Confined and Unconfined Geological CO2 Reservoirs. (July 2017) - Kabirzadeh, Hojjat; Sideris, Michael G.; Shin, Young J.; Kim, Jeong W.
Abstract: The surface gravity effect of the injected CO2 into geological reservoirs has always been assumed to be a negative signal, and to be dependent on the injected CO2 mass and the reservoir depth. Nonetheless, certain geological CO2 reservoirs with specific characteristics experience porosity changes and exhibit large ground surface deformation. The gravimetric effect as a result of mass balance changes in such reservoirs is modeled as a positive signal. Our investigations on the geomechanical properties of the two different types of reservoirs demonstrate the indirect dependency of gravity signal on a few other characteristics, like reservoir size, porosity, and permeability.